Effect of Temperature on The Degradation of Aldrin Residues in Sandy Loam Soil - Kushwaha, K S K; Gupta, H C L; Kavadia, V S (Annals of Arid Zone, 2016)
The persistence of aldrin in sandy loam soil was for short period at lower temperature (25'C) than at higher temperatures (35' and 45Â°C). The calculated half life values of about 49, 143 and 177 days for 6 ppm and 59, 164 and 200 days for 12 ppm dosages at three temperatures also corroborate the above findings. The conversion of aldrin into dieldrin was also found to increase with the rise in temperature fol a period of 6 months but the converted dieldrin declined with the passage of time.